Role of peptide hormones in regulation of plant growth and development and their adaptation to environmental factors - Filiptsova, Halina G. (Experimental Biology and Biotechnology, 2024)
Plant peptide hormones are a class of signaling substances involved in the regulation of growth and development processes, as well as the adaptation of plant organisms to stress. Induction of genes, which encode precursors of peptide hormones, occurs in response to a variety of external and internal stimuli. Peptide hormones are perceived by specific receptors of plant cells and trigger a multi-level signaling system that ensures the coordination of cellular processes under changing environmental conditions, the development of protective reactions and the formation of immunity. This work analyses recent studies on the structure, functional activity and signaling mechanisms of the main groups of plant peptide hormones.
Keywords: plant peptide hormones; signaling mechanisms; regulation of growth and development; plant resistance